Oil Essential Mouthwashes Antibacterial Activity against Aggregatibacter actinomycetemcomitans: A Comparison between Antibiofilm and Antiplanktonic Effects - Matteo Erriu; Francesca Maria Giovanna Pili; Enrica Tuveri; Daniela Pigliacampo; Alessandra Scano; Caterina Montaldo; Vincenzo Piras; Gloria Denotti; Andrea Pilloni; Valentino Garau; Germano Orrù (International Journal of Dentistry)
The aim of this work is to determine the antibacterial activity of three marketed mouthwashes on suspended and sessile states of Aggregatibacter actinomycetemcomitans. The efficacy of two commonly used products in clinical practice, containing essential oils as active ingredients (menthol, thymol, methyl salicylate, and eucalyptol) in association with or without alcohol, has been evaluated in comparison with a chlorhexidine-based mouthwash. The microtiter plate assay, in order to obtain a spectrophotometric measurement of bacterial responses at growing dilutions of each antiseptic, was used for the study. The analysis revealed that a good antibacterial activity is reached when the abovementioned mouthwashes were used at concentration over a 1/24 dilution and after an exposure time of 30 seconds at least. In conclusion, the alcoholic mouthwash appears to have a better biofilm inhibition than its antiplanktonic activity while the nonalcoholic product demonstrates an opposite effect with a better antiplanktonic behavior.